Digital Development And Improving Participatory Budgeting As A Mechanism To Empower Citizens To Effectively Participate In Local Governance - Ouikene FAZIA (Akofena)
Abstract: Participatory budgeting is a democratic and participatory system that empowers citizens to mobilize, propose, discuss, and select projects aimed at improving the living environment and enhancing the quality of life. In most international experiences related to participatory budgeting, the state prioritizes the projects proposed by the population. Local councils adopt these projects in the budget for the following year. Participatory budgeting is a crucial mechanism for involving citizens in directing public funds and allocating resources to projects that are supported by the citizens. It aims to prevent corruption and mismanagement. Citizens' engagement in the participatory budgeting process reflects their trust in government administrations and local councils, as well as their desire to participate in selecting and implementing projects that align with their needs and perceptions of sound local governance. Technological advancements have brought about radical changes in the concept of participatory budgeting. The digitization of participatory budgeting has enabled citizens to take part in managing their affairs and directing government projects toward their areas of interest and priorities. It has also overcome many challenges of representative democracy, notably the increasing number of citizens and the difficulty of individually reaching them. Technological development has facilitated communication with citizens through digital platforms created for this purpose. Moreover, it has contributed to reducing the burden of communication and minimizing the negative aspects of managing public funds. Keywords: Participatory budgeting, citizen, Local governance, Participatory democracy, Digitization.